Clinical and laboratory characteristics of patients associated with severe COVID-19 infection and death at a tertiary care hospital in Sri Lanka - I. Wettasinghe; S. M. Samarasinghe; S. Wijekoon; A. Sugathapala; M. I. Mujaheit; C. Seneratna; C. N. Wijekoon (Sri Lanka College of Internal Medicine, 2024)
Introduction: COVID-19 caused a massive burden to the health sector in Sri Lanka. This study aims to describe the clinical and laboratory characteristics associated with severe COVID infection and death in patients with moderate or severe COVID-19. Methods: This descriptive cross-sectional study was carried out from November 2021-June 2022 at a Teaching Hospital in Colombo. Consecutive sampling of adults admitted to hospital with moderate or severe COVID-19 was done. Data was collected from patient interviews and medical records. Results: The study population consisted of 388 patients. Mean age (SD) was 61.1 (±14.7) years and 56.4% were men. In-hospital deaths were 39%. Shortness of breath was the commonest presenting complaint (89.4%). Death was more common among those with the following symptoms as opposed to those without; fever (49.3% vs 27.7%, p< .001), cough (64.2% vs 23.2%, p< .001) and chest pain (70.5% vs 34.9%, p < .001). Other factors associated with death were male gender (44.2% vs 32.1 %, p= .016), age >60years (66.5 vs 10.1, p< .001), diabetes (47.2% vs 23.7%, p< .001), hypertension (61% vs 23.5, p< .001), ischemic heart disease (78.6% vs 30.1%, p< .001), COPD (90.0% vs 35.8%, p< .001) and smoking (60.3% vs 34%, p< .001). Symptoms, demographics and comorbidities associated with severe disease compared to moderate disease were similar to those associated with in-hospital deaths. High white cell count, high CRP, low pH and low SpO2 on admission were significantly associated with death as well as severe disease. Conclusions: Clinical and laboratory characteristics associated with death in patients with COVID-19 were similar to those with severe COVID. These parameters help to detect patients who need close monitoring and more intensive management.